On the Effects, Problems, and Countermeasures of Undergraduate Teaching Evaluation in Higher Education. Issue 1 (3rd March 2016) - Xianjun, Liu; Yang, Yu; Junchao, Zhang; Shuguang, Wei; Ling, Ding
Abstract: The Undergraduate Teaching Evaluation of General Institutions of Higher Education from 2003 to 2008 was the largest-scale evaluation in Chinese higher education history. It exerted a tremendous influence as a key exploration of quality assurance with Chinese characteristics. Based on existing research, this study combines quantitative and qualitative methods to probe the evaluation's effects as well as problems and countermeasures. Major effects included establishing an undergraduate teaching baseline, fostering distinction, faculty development, teaching reform, and standardized teaching management. Problems included applying the same evaluation criteria to all institutions, unclear positioning of provincial educational authorities, weak reform efforts, inflated excellent ratings, and a timing imbalance. Suggested countermeasures include regular statutory evaluations, guidance for categorized evaluation criteria, internal quality assurance systems, teaching databases, active institutional research, and rational higher education management.